Tiger Parenting and American Inequality: An Essay on Chua and Rubenfeld’s The Triple Package: How Three Unlikely Traits Explain the Rise and Fall of Cultural Groups in America - Lundberg, Shelly (Journal of Economic Literature, 2015)
The role of culture in the creation and persistence of racial and ethnic inequalities has been the focus of considerable controversy in the social sciences. In The Triple Package: How Three Unlikely Traits Explain the Rise and Fall of Cultural Groups in America, a new book intended for a popular audience, “tiger mom” Amy Chua and Jed Rubenfeld argue that relatively successful ethnic, religious, and national origin groups in the United States possess a common set of culturally determined traits that drive this success: a sense of group superiority, individual insecurity, and good impulse control. The book is an unscholarly romp through fields of ethnic stereotypes and immigrant anxiety that relies on anecdote, rather than data, and that ignores the selectivity of immigrant flows. In their insistence on the need for the whole triple package, however, the authors raise issues relevant to current research on noncognitive skills—that there are important trait–environment interactions in the determinants of economic success, and that the source and impact of aspirations deserves greater attention. (JEL D63, J15, J24, Z12, Z13)